The Stylistics Comparison on the Dialogues of the People of Hell in film Siksa Neraka with Quran - Muhammad Athari Basir; Mohd Adi Amzar Muhammad Nawawi; Engku Muhammad Syafiq Engku Safruddin; Muhammad Hakim Kamal; Aishah Isahak (Elite Scientific Forum, Pakistan, 2025)
Indexed by Scopus (Tier 2)